Effects of melatonin on planaria head regeneration are dependent on both timing and duration of exposure - Simon C. Beeching; Hanna E. Ruland; Katelyn M. Sparks (Physiological Reports)
Abstract Melatonin is a multifunctional biomolecule with demonstrated stimulatory, inhibitory, and antioxidant effects, including both receptor‐mediated and receptor‐independent mechanisms of action. One of its more perplexing effects is the disruption of regeneration in planaria. Head regeneration in planaria is a remarkable phenomenon in which stem cells (neoblasts) migrate to the wound site, proliferate, then differentiate into all functional tissue types within days of injury. We investigated how both the timing and duration of melatonin exposure affect head regeneration in the planaria Phagocata gracilis (Haldeman). Our results demonstrate that P. gracilis is capable of recovery from the melatonin‐induced delay of regeneration and reveal the time required to recover to control levels. Further, we found evidence of regenerative stage‐specific responses to discontinuous melatonin exposure, including non‐inhibitory effects. Further exploration of melatonin's effects on regeneration can be targeted to specific regenerative processes, and the possibility of multiple mechanisms of action should be recognized.